1985
DOI: 10.1113/jphysiol.1985.sp015824
|View full text |Cite
|
Sign up to set email alerts
|

Membrane voltage, resistance, and channel switching in isolated mouse fibroblasts (L cells): a patch‐electrode analysis.

Abstract: SUMMARY1. The whole-cell patch-electrode technique of Fenwick, Marty & Neher (1982) has been applied to single suspension-cultured mouse fibroblasts. Seals in the range of 10-50 GQ were obtained without special cleaning of the cell membranes.2. Rupture of the membrane patch inside the electrode was accompanied by a shift of measured potential into the range -10 to -25 mV, but in most cases with little change in the recorded resistance. The latter fact implied that (i) the absolute resistance of the cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
4
20
1
Order By: Relevance
“…The high membrane resistance of 4·1 ± 0·1 GÙ measured in human atrial fibroblasts corresponds to the values of membrane resistance for fibroblasts from different species (Hosoi & Slayman, 1985;Lovisolo et al 1988). Membrane resistance for cardiac fibroblasts represented in the literature ranges from 0·5 to 25 GÙ (Rook et al 1989;Kohl et al 1992Kohl et al , 1994Kondratjev et al 1993).…”
Section: Baseline Electrophysiological Propertiesmentioning
confidence: 99%
“…The high membrane resistance of 4·1 ± 0·1 GÙ measured in human atrial fibroblasts corresponds to the values of membrane resistance for fibroblasts from different species (Hosoi & Slayman, 1985;Lovisolo et al 1988). Membrane resistance for cardiac fibroblasts represented in the literature ranges from 0·5 to 25 GÙ (Rook et al 1989;Kohl et al 1992Kohl et al , 1994Kondratjev et al 1993).…”
Section: Baseline Electrophysiological Propertiesmentioning
confidence: 99%
“…One possibility could be that all cells express 'K+ leak' whose activity depends on a diffusible factor which dialyses away in whole cell but does not pass through gap junctions. A patchclamp study in mouse L cells (Hosoi & Slayman, 1985) suggested that the resting membrane conductance is K+ dominated which decayed over a period of minutes. An interesting hypothesis to consider, however, is the possibility that the establishment of open gap junctions between cells causes the formation of voltage-independent K+ channels.…”
Section: Voltage-independent Channelsmentioning
confidence: 99%
“…Taken together, these results are in accord with the concept that the protein encoded in WS3-10 mRNA leads to an alteration in one or more intracellular Ca2+-dependent processes during HDF senescence. Ca2+ flux activates several physiologic functions in nonexcitable cells, including gene expression, initiation of DNA synthesis, entry into mitosis, and cell contractility and motility (1)(2)(3)(4)(5)(6)(7). Although we used a standard pipet solution (Ca2+ at 110 nM) to dialyze the interior ofthe cell, membrane currents were measured within 1.5 min after rupture ofthe membrane, before [Ca2+]i of HDFs has been quantified by others under a variety of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, slope conductances of senescent and WS cells measured in response to 20-mV hyperpolarizing pulses from the holding potential of -40 mV were 35% and 23%, respectively, of those in control young HDFs ( perhaps to "age" heterogeneity, due to the admixture of senescent cells that exists among young cells in mass cultures (11,12). Internal dialysis of WS HDFs with pipet solutions containing 5 Translation of WS3-10 mRNA in Vitro. To confirm that the WS3-10 gene sequence does in fact express a protein, we translated WS3-10 mRNA in a rabbit reticulocyte lysate (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation